2021
DOI: 10.1016/j.ijid.2020.09.1473
|View full text |Cite
|
Sign up to set email alerts
|

Human respiratory viruses, including SARS-CoV-2, circulating in the winter season 2019–2020 in Parma, Northern Italy

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
66
1
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(84 citation statements)
references
References 23 publications
7
66
1
10
Order By: Relevance
“…No co-infection between SARS-CoV-2 and other respiratory viruses was found. This result is in agreement with those reported in the same area in a different period (1 December 2019–31 March 2020) in which among in- and out-patients, viral mixed infections were observed only in three children younger than 1 year old when samples of the upper respiratory tract (two nasopharyngeal swabs and one throat swab) were analyzed [ 18 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…No co-infection between SARS-CoV-2 and other respiratory viruses was found. This result is in agreement with those reported in the same area in a different period (1 December 2019–31 March 2020) in which among in- and out-patients, viral mixed infections were observed only in three children younger than 1 year old when samples of the upper respiratory tract (two nasopharyngeal swabs and one throat swab) were analyzed [ 18 ].…”
Section: Discussionsupporting
confidence: 92%
“…The qualitative detection of SARS-CoV-2 RNA was carried out for all samples by using a real-time PCR after reverse transcription (RT-PCR) panel according to the Centers for Disease Control and Prevention (CDC, Atlanta, GA, USA) protocol, with some modifications as previously reported [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our ILI series, no SARS-CoV-2-positive cases were identified before week 10-2020, which is in line with the findings obtained in other molecular studies carried out on Italian SARS-CoV-2 strains identified in symptomatic individuals [29][30][31]. On the other hand, ILI surveillance carried out on a greater number of individuals by a larger number of sentinel practitioners may have been able to detect SARS-CoV-2 at an earlier stage of its introduction in Italy, as the first two imported cases were detected at the end of January [32], approximately a month before the first Italian COVID-19 case was reported in Lombardy.…”
Section: Discussionsupporting
confidence: 92%